Picture‐naming test for a linguistically diverse population with cognitive impairment and dementia. Issue 4 (6th May 2022) - Paplikar, Avanthi; Varghese, Feba; Alladi, Suvarna; Vandana, V. P.; Darshini, K. J.; Iyer, Gowri K.; Kandukuri, Rajmohan; Divyaraj, Gollahalli; Sharma, Meenakshi; Dhaliwal, R. S.; Kaul, Subhash; Saroja, Aralikatte Onkarappa; et al.
Abstract: Background: Picture‐naming tests (PNTs) evaluate linguistic impairment in dementia due to semantic memory impairment, impaired lexical retrieval or perceptual deficits. They also assess the decline in naming impairment at various stages of dementia and mild cognitive impairment (MCI) that occurs due to progressive cognitive impairment. With the increasing numbers of people with dementia globally, it is necessary to have validated naming tests and norms that are culturally and linguistically appropriate. Aims: In this cross‐sectional study we harmonized a set of 30 images applicable to the Indian context across five languages and investigated the picture‐naming performance in patients with MCI and dementia. Methods & Procedures: A multidisciplinary expert group formed by the Indian Council of Medical Research (ICMR) collaborated towards developing and adapting a picture naming test (PNT) known as the ICMR‐PNT in five Indian languages: Hindi, Bengali, Telugu, Kannada and Malayalam. Based on cross‐cultural adaptation guidelines and item‐wise factor analysis and correlations established separately across five languages, the final version of the ICMR‐PNT test was developed. A total of 368 controls, 123 dementia and 128 MCI patients were recruited for the study. Psychometric properties of the adapted version of the ICMR‐PNT were examined, and sensitivity and specificity were examined. Outcomes & Results: The ICMR‐PNT scores in all languages combined were higher in controls compared with patients with dementia and MCI ( F 2, 615 = 139.85; p < 0.001). Furthermore, PNT scores for MCI was higher in comparison with patients with dementia in all languages combined ( p < 0.001). The area under the curve across the five languages ranged from 0.81 to 1.00 for detecting dementia. There was a negative correlation between Clinical Dementia Rating (CDR) and ICMR‐PNT scores and a positive correlation between Addenbrooke's Cognitive Examination—III (ACE‐III) and ICMR‐PNT scores in control and patient groups. Conclusions & Implications: The ICMR‐PNT was developed by following cross‐cultural adaptation guidelines and establishing correlations using item‐wise factor analysis across five languages. This adapted PNT was found to be a reliable tool when assessing naming abilities effectively in mild to moderate dementia in a linguistically diverse context. What this paper adds: What is already known on this subject: Picture‐naming evaluates language impairment linked to naming difficulties due to semantic memory, lexical retrieval or perceptual disturbances. As a result, picture naming tests (PNTs) play an important role in the diagnosis of dementia. In a heterogeneous population such as India, there is a need for a common PNT that can be used across the wide range of languages. What this study adds to existing knowledge: PNTs such as the Boston Naming Test (BNT) were developed for the educated, mostly English‐speaking, Western populations and are not appropriate for use in an Indian context. To overcome this challenge, a PNT was harmonized in five Indian languages (Hindi, Bengali, Telugu, Kannada and Malayalam) and we report the patterns of naming difficulty in patients with MCI and dementia. The ICMR‐PNT demonstrated good diagnostic accuracy when distinguishing patients with mild to moderate dementia from cognitively normal individuals. What are the potential or actual clinical implications of this work?: With the growing number of persons suffering from Alzheimer's disease and other forms of dementia around the world, its critical to have culturally and linguistically relevant naming tests and diagnosis. This validated ICMR‐PNT can be used widely as a clinical tool to diagnose dementia and harmonize research efforts across diverse populations.